Analysis of Workload, Courier Performance, and Work Motivation at the J&T Express DC Expedition Service Company in Palangka Raya - Anastasia Dhea Amanda; Aprilita (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This study aims to determine the effect of workload on courier performance with work motivation as an intervening variable.Design/Methodology/Approach – The analytical method used in this research is quantitative. The population and sample in this study were all J&T Express DC couriers in Palangka Raya City, totaling 45 people using the census technique. The analytical method used in this study is Partial Least Square (PLS) with the SmartPLS 4.0.9.3 analysis tool.Findings – The results of this study indicate that workload has a negative and significant effect on performance, the workload has a negative and significant effect on work motivation, work motivation has a significant positive effect on performance, and work motivation has a negative and significant role in mediating the relationship between workload and the performance of the J&T Express DC courier, Palangka Raya City